Evaluation of differentiation districts of the Republic Serbia in the process of rural development - Nikolić Đorić, Emilija; Čobanović, Katarina (Economics of Agriculture, 2010)
This paper analyses some important indicators of rural development, such as: national income per capita, the ratio of maximal and minimal value of national income per capita and the share of the national income from agriculture in the overall national income. The indicators are analysed for 24 districts of the Republic of Serbia and the city of Belgrade, without Kosovo and Metohia. The existing statistical data are used in this analysis as the basis for evaluating the level of development and differentiation of the districts of Serbia. The analysed indicators refer to three time sections, in the following years 1997, 2002 and 2005.